The Poor as Symptom: A Lacanian Reading of the Option for the Poor - Checketts, Levi (Religions, 2023)
Latin American liberation theology contributed perhaps the most significant theological contribution of the twentieth century in the “preferential option for the poor”. This insight has been an uneasy call to conscience for the magisterial Catholic Church, which has often buttressed the positions of the powerful. However, despite the central significance of this discovery, liberation theologians themselves often betray their own positions by romanticizing the poor, speaking on their behalf, diluting the meaning of poor and other such seeming shortcomings. This article argues that the incongruence regnant in discussions of the preferential option can best be understood through the Lacanian notion of a “symptom”. As “woman is the symptom of man”, the poor are the symptom of the upper classes. In order for nonpoor to understand their own socioeconomic position—including academically trained clergy—they must posit the poor as an Other against whom they understand themselves. As such, reaching “the poor” is an impossibility for anyone who is in a position to truly advocate for them. However, the insight of the preferential option tells us that the impossibility should be pursued nonetheless, with full understanding that it is an impossibility.